التنبؤ بعدد المصابين بسرطان الدم باستخدام نماذج السلاسل الزمنية من "2015-2017" في محافظة أربيل - عمر، برى خان عبدالله Omar, Berri Khan Abdullah (جامعة صلاح الدين, 2018)
يهدف هذا البحث إلى استخدام أحدى الأساليب الإحصائية الكفوءة للتبوء بمرض السرطان، والتي هو عبارة عن تكاثر الخلايا بشكل غير طبيعي ومنظم في الجسم لتصبح شاذة وتتكاثر دون تحكم وتخرج عن خط النمو الطبيعي، تعتبر إنجاز بحث في هذا المجال لابد أن تستند على التحليل الإحصائي العلمي الذي يعتمد على الأساليب والطرق الإحصائية الكفوءة بمعايير ومقاييس كمية وعلمية عالية المعنوية، لذا تم استخدام تحليل السلاسل الزمنية للتنبؤ بعدد المصابين بسرطان الدم خلال السنة القادمة أو فيما سنواجهه في المستقبل القريب وذلك اعتماداً على البيانات الحقيقية التي أخذت من دائرة الصحة ومستشفى نانةكةلى الخاصة بسرطان الدم من (2015 – 2017) والهدف من استخدام تلحيل الإحصائي للسلسلة الزمنية للبيانات هو فهم خصائصها الأساسية (تغيراتها ودوراتها وتذبذباتها غير المنتظمة) ومن ثم التقدير والتنبؤ بسلوك السلسلة الزمنية في المستقبل لكلا الجنسين وتم إيجاد أفضل نموذج بالاعتماد على قيمة متسوط مربعات الخطأ (MSE) وتبين من نتائج تحليل السلسلة الزمنية لكلا الجنسين أن هناك زيادة في عدد المصابين بسرطان الدم أي تتكاثر مع مرور الزمن اعتمادا على أقل قيمة من المتوسط مربعات الخطأ من نموذج المقترح (ARIMA 0,1,0) الإناث ونموذج المقترح (ARIMA 1,0,0) للذكور.
Cancer is an abnormal reproduction of cells and irregular in the body, it becomes abnormal and multiplies without controlling and out of the natural growth line, one of the modern theories says that the cause is a simple genetic defect that cannot be observed by the immune system and this defect with time causes the cell to come out of the control Then the cancer will appear. The completion of researches such as this type of specifications and characteristics must be based on the scientific analysis which depends on the efficient statistical methods with the quantitative measures and scientific high significant. Therefore, the time series have been used to predict the number of people infected the cancer over the next year or what we face it in the sooner future depending on the real data from (2015-2017) that taken from the department of the health and Nanakaly Hospital. The aim of using the statistical analysis of the time series analysis is to understand its basic characteristics (changes, cycles and irregular fluctuations), estimate and predict the behavior of the time series in the future for both of (Female and Male) and finding the best model by relying on the value of mean squares error (MSE), the results of time series analysis for both (Female and Male) shows that there is increased in the number of infected or multiplies over the time.
Keywords: الانحدار الذاتي -- السلاسل الزمنية -- سرطان الدم